New Paradigms in Access to Scientific Information and the Role of the Internet - Bülent Karasözen (Türk Kütüphaneciliği)
The Internet transforms the scholarly communication world-wide. Electronic preprint archives, electronic journals, discussion groups are some of the new ways to get acccss to information. This paper discusses some of these new developments from the perspective of scholarly communication. Among the topics covered are quality control of scientif ic publications in the electronic world, information overload, the impact of electronic publishing on librai'ies and publishers, and the economics of electronic publishing.